Akad Ijarah Muntahiyah Bit Tamlik: Tantangan dan Peluang - Romi, Muhammad; Miftahurrahmah, Miftahurrahmah; Mawardi, Mawardi (Universitas Islam Lamongan, 2025)
This study aims to analyze the validity of IMBT, identify regulatory and implementation challenges, and map opportunities for its future development. The research method used is library research with a descriptive qualitative approach. Data were obtained through a literature review of laws and regulations, fatwas, books, and journals related to IMBT. The analysis was conducted by examining the conformity of IMBT provisions according to fiqh muamalah and national regulations, including DSN-MUI Fatwa No. 27/DSN-MUI/III/2002, the Compilation of Sharia Economic Law, the Sharia Banking Law, and Bank Indonesia regulations. The results show that IMBT has a strong legal basis both in sharia and positive law. However, its implementation faces several obstacles such as the lack of specific regulations that regulate it in detail, lack of synchronization of regulations between authorities, differences in interpretation of asset maintenance and ownership transfer mechanisms, the risk of default, and low sharia financial literacy. Therefore, it is recommended to harmonize regulations between authorities, establish a special law for IMBT, develop transparent contract standards, improve Islamic financial literacy, and implement appropriate risk management to strengthen the attractiveness of IMBT in Islamic financing.